Direct Torque Control Strategies of Electrical Machines - Ben Salem, Fatma (IntechOpen, 2021)
This book deals with the design and analysis of Direct Torque Control (DTC). It introduces readers to two major applications of electrical machines: speed drive and position control and gives the readers a comprehensive overview of the field of DTC dedicated to AC machines. It includes new DTC approaches with and without control of commutation frequency. It also covers DTC applications using artificial intelligence. The book combines theoretical analysis, simulation, and experimental concepts.To make the content as accessible as possible, the book employs a clear proposal in each chapter, moving from the background, to numerical development, and finally to case studies and illustrations. The book is a wide-ranging reference source for graduate students, researchers, and professors from related fields and it will benefit practicing engineers and experts from the industry.